Humanoid Dancer Robot Movement Synchronization System with Zigbee - Ponco Sukaswanto; Abdul Fadlil (Buletin Ilmiah Sarjana Teknik Elektro, 2020)
This research proposes a wireless communication between two dancer robots using zigbee to overcome the differences in movement between the robots in order to dance in harmony. The robotic music processor uses Audio Analyzer V2.0 which functions to get 7 frequency values for the music being played. The frequency will be processed by Arduino to determine the condition of the music on and off which will be sent to each robot via the XBee S2C module using the Zigbee method, namely with 1 master and 2 routers. The result is that the music processing system becomes more robust because it uses the Zigbee method. By using the Zigbee method, robot 1 and robot 2 can also communicate with each other because with this method, fellow routers can exchange data. The robot produced by this study can already distinguish the conditions when music is playing or muted, and between robot 1 and robot 2 can communicate with each other. Communication between robots functions so that when one of the robots is late in getting data, the other robots will wait until the late robot completes its movements so that robot 1 and robot 2 are back in sync.